2009
DOI: 10.1177/0883073808324533
|View full text |Cite
|
Sign up to set email alerts
|

Early Working Memory in Children Born With Extremely Low Birth Weight: Assessed by Object Permanence

Abstract: Object permanence is considered the earliest method for assessing working memory. Factors affecting object permanence performance in a sample of two hundred and thirty-three 18- to 22-month olds born with extremely low birth weight were examined. It was hypothesized that object permanence would be directly related to emotional and attention regulation, that children with lower birth weight and higher illness severity would have more difficulty on the object permanence task, and that no ethnic/racial difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…This confirms our previous findings in regards to object permanence and cognition as measured by the BSID-II, 18 and provides additional evidence that object permanence is a culturally neutral measure of early working memory. This is an important finding, as tests of cognition are influenced by race/ethnicity, 19 maternal education, and parental stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This confirms our previous findings in regards to object permanence and cognition as measured by the BSID-II, 18 and provides additional evidence that object permanence is a culturally neutral measure of early working memory. This is an important finding, as tests of cognition are influenced by race/ethnicity, 19 maternal education, and parental stress.…”
Section: Discussionsupporting
confidence: 90%
“…25 Our finding that object permanence was associated with cognition and language scores on the BSID-III indicates that it could potentially augment research by providing an additional measure of development that is potentially free of socio-economic and racial/ethnic biases. 18 Better understanding of early executive functioning in extremely preterm children could lead to earlier diagnosis and improved interventions for children born preterm. In conjunction with the BSID-III cognitive score, a measure of object permanence may improve our detection of ongoing problems with executive function at 18–22 months, which is highly related to learning difficulties later in life.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study using the BSID-II, however, race and ethnic differences remained even after adjustment. 9 This difference may be due to the inclusion of a separate language domain in the BSID-III. Ethnic and cultural influences may be of less concern for cognitive development than previously believed, and our results highlight the importance of conducting future studies of assessment of language development in this population.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated higher overall BSID-II MDI scores in White children than in Hispanic-White or Black children that were not explained by socioeconomic status or maternal education. 9 The cause of this difference is undetermined. A third edition of the Bayley Scales of Infant and Toddler Development (BSID-III) has been developed, 10 and is now being used exclusively throughout the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network (NRN) centers.…”
mentioning
confidence: 99%
“…Only one study has reported associations between infant temperament and working memory; however, the work was done with extremely low birth weight infants when they were 18-22 months of age (Lowe, MacLean, Shaffer, & Watterberg, 2009). Keenan (2002) reported that negative affect resulted in lower levels of performance on the A-not-B task, but this was measured as negative emotion (on a scale from 1 to 5) during participation in A-not-B testing, not as a temperamental trait.…”
Section: Temperamentmentioning
confidence: 99%